Präferenzen von Landwirten bei der Gestaltung von Substratlieferverträgen für Biogasanlagen: Ein Choice-Experiment : a choice experiment; Farmers' Preferences regarding the Design of Substrate Supply Contracts for Biogas Plants: A Choice Experiment - Christian Reise; Ulf Liebe; Oliver Mußhoff (German Journal of Agricultural Economics (GJAE), 2012)
– Substrate supply, which is often regulated by corresponding contracts, is essential for a sustainable expansion of renewable energies generated in biogas plants. To the authors' knowledge, no quantitative investigations of farmers' preferences with regard to supply contracts for biogas plants have been carried out so far. Hence, it has been only possible to a limited extent to make predictions for a targeted ar-rangement of supply contracts. We, therefore, investigated, to what extent different factors have relevance for the conclusion of substrate supply contracts. This has been done by conducting a survey with 178 German farm managers. The survey included a choice experiment in which participants were confronted with different contract features. These features were varied systematically and thus revealed the influence of each individual feature on the probability of contract conclusion. It becomes clear that the farmers who were interviewed preferred to conclude contracts with other farmers or with a bioenergy village rather than with external investors. The probability of contract conclusion decreases with an increasing lifetime of the contract. However, a contract with a higher sales price is more attractive for the farmers. The investigation of the characteristics of respondents shows that the amount of the premium for one additional year of contractual lifetime depends on the individual valuation of the entrepreneurial freedom of the respective farm manager. It cannot be established that risk-averse farmers tend to prefer contracts with fixed prices over contracts with price adjustment clauses. In addition, there are no great differences in the choice behavior of farmers who have already signed a substrate supply contract and farmers without this experience.
Keywords: 330